To Form or Not to Form: What (to) Form? An Unabridged List of Sustainables - Isben Onen (Anuari d’Arquitectura i Societat)
This compact scrutiny delves into the intricate and multifaceted relationship between architecture, human experience, and its surroundings. It places architecture within a transdisciplinary framework that extends far beyond the conventional boundaries of erecting physical structures. Instead, it encompasses a rich tapestry of philosophy, culture, history, and various intellectual domains. Architecture, as argued here, occupies a unique space that is simultaneously abstract and tangible. In this capacity, it serves as a catalyst for critical thinking and reflective exploration of what to sustain. At the heart of this discourse lies the concept of architectural form, which emerges as a central theme. Architectural form is portrayed as a dynamic and abstract entity, particularly in its nascent stages, where it plays a pivotal role as a proposal for the order and harmony inherent in the built environment.